2021
DOI: 10.3390/cancers13246214
|View full text |Cite
|
Sign up to set email alerts
|

The Hippo Signaling Pathway in Cancer: A Cell Cycle Perspective

Abstract: Cell cycle progression is an elaborate process that requires stringent control for normal cellular function. Defects in cell cycle control, however, contribute to genomic instability and have become a characteristic phenomenon in cancers. Over the years, advancement in the understanding of disrupted cell cycle regulation in tumors has led to the development of powerful anti-cancer drugs. Therefore, an in-depth exploration of cell cycle dysregulation in cancers could provide therapeutic avenues for cancer treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 271 publications
(384 reference statements)
0
28
0
Order By: Relevance
“…Multiple pathways enriched for intergenic variants corresponding genes/non-coding RNAs are overlapping with the enriched pathways for genes/non-coding RNAs with variants in intronic, untranslated region (UTR), and non-coding RNA regions, including Axon guidance (FDR = 9.07E-4 & 4.31E-8, respectively), Cell adhesion (FDR = 4.76E-3 & 2.69E-4), Pathways Regulating Hippo Signaling (FDR = 3.74E-4 & 6.52E-10), Splicing factor NOVA regulated synaptic proteins (FDR = 0.003 & 1.56E-6), Hippo-Merlin Signaling Dysregulation (FDR = 0.003 & 1.78E-6), and Ectoderm Differentiation (FDR = 0.008 & 3.8E-5). Genetic variants and observed altered expression of the Hippo pathway have the unique capacity to lead to tumorigenesis and thereby, promote the migration, invasion, and malignancy of cancer cells through cell cycle regulation [20,21]. NOVA factors promote cell proliferation, colony formation, migration, and invasion by interacting with miRNA in cancer cells [22].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple pathways enriched for intergenic variants corresponding genes/non-coding RNAs are overlapping with the enriched pathways for genes/non-coding RNAs with variants in intronic, untranslated region (UTR), and non-coding RNA regions, including Axon guidance (FDR = 9.07E-4 & 4.31E-8, respectively), Cell adhesion (FDR = 4.76E-3 & 2.69E-4), Pathways Regulating Hippo Signaling (FDR = 3.74E-4 & 6.52E-10), Splicing factor NOVA regulated synaptic proteins (FDR = 0.003 & 1.56E-6), Hippo-Merlin Signaling Dysregulation (FDR = 0.003 & 1.78E-6), and Ectoderm Differentiation (FDR = 0.008 & 3.8E-5). Genetic variants and observed altered expression of the Hippo pathway have the unique capacity to lead to tumorigenesis and thereby, promote the migration, invasion, and malignancy of cancer cells through cell cycle regulation [20,21]. NOVA factors promote cell proliferation, colony formation, migration, and invasion by interacting with miRNA in cancer cells [22].…”
Section: Discussionmentioning
confidence: 99%
“…Loss or overactivation of the Hippo pathway may lead to abnormal cell growth and tumorigenesis. In previous studies, researchers found that genes related to the Hippo pathway are often abnormally expressed in various cancers such as liver cancer, colorectal cancer, and lung cancer, and are related to the occurrence and development of tumors (Han, 2019;Xiao and Dong, 2021). The core components of the mammalian Hippo signaling pathway include cytoplasmic kinase module and a nuclear transcriptional module.…”
Section: Discussionmentioning
confidence: 99%
“…In cancer cells, the aberrant activity of the cell cycle is due to mutations in genes encoding cell cycle proteins or components of upstream signaling pathways. For example, CDKN2A (encodes tumor suppressors p16 INK4A and p14 ARF ) and CDKN2B genes (encodes tumor suppressors p16 INK4A -p14 ARF and p15 INK , respectively) are commonly deleted, or its promoter is silenced by methylation in human cancers [ 210 , 211 ]. Around 54% of glioblastomas present deep deletion of cdkn2a or cdkn2b genes.…”
Section: Oncogenic Signaling Pathwaysmentioning
confidence: 99%